Branch Campuses of State Universities and Colleges in Region III: Analysis and Evaluation - Gamboa, Jerame (Technium Social Sciences Journal, 2020)
The whole world is one in making education accessible to all. It is in this mission that gives birth to the existence of different branch campuses. The guidelines in the establishment of the branch campuses are reflected on the Manual of Regulations for Private Higher Education of 2008 and CHED Memorandum Order no. 27 series of 2009. At present, there are 388 public branch campuses in the Philippines. However, it has to be emphasized that the public branch campuses in the Philippines are temporary and are not part of the charter of the SUCs. This study analyzed and evaluated the present conditions of the branch campuses of the State Universities and College in Region III. Evaluative research was employed, with the use of a questionnaire adopted from AACCUP, interview, documentary materials of Accreditation results to gather data from the campus administrators. Results showed that the branch campuses were built to make education accessible to the nearby communities. The SUCs Branch Campuses were outstanding in their administration, VMGO, faculty, curricular offerings and instruction, and support for students. The laboratories and facilities were evaluated as inadequate. Also, no variations were identified on the branch campuses’ researches and extension services. The area of library was found to be adequate. Funding was the main problem that led to some other problems, issues, and concerns.Policy makers should create a manual for the establishment of branch campuses where uniformity on operations and allocation of budget should be clearly stated so that improvement on their infrastructures, facilities, laboratories, and equipment can be planned and actualized. Also, marketing strategies should be effective and long-term development plan should be conceptualized to assure sustainability